CYBER CRIME AND THE PROTECTION OF WORKING WOMEN A SOCIO LEGAL STUDY (International Journal of Food and Nutritional Sciences, 2022)
The goal of this paper is to evaluate the raw data and turn it into something useful. This chapter is a collection of primary data gathered during fieldwork. After evaluating the data, broad observations are made. Statistical Package for Social Sciences version 26.0 and MS-Excel were used to analyze the data. Statistical tests of various types were used based on the variables under investigation. This chapter presents the deductions and conclusions obtained from the results of these tests.